Conocimiento y uso del condón masculino en estudiantes de secundaria de una institución educativa de zona periurbana de Iquitos 2024 - Barrantes Vela, Gerson Daniel (2025)
The objective of this study was to determine the relationship between knowledge and the use of male condoms among fourth- and fifth-year secondary school students of both sexes at Santa Clara de Nanay Educational Institution No. 60027 in Iquitos, during 2024. This was a quantitative, non experimental, and correlational study. The data collection technique used was a survey, and two instruments were applied: a questionnaire on knowledge about male condom use (validity 93.3%, reliability 96.0%) and a checklist (validity 96.3%, reliability 94.0%). The results showed that 66.7% of the students had inadequate knowledge, while 33.3% demonstrated adequate knowledge. Regarding condom use, 70.4% of the students reported not using it, while 29.6% did. Among those who used condoms, 62.5% did so incorrectly and 37.5% correctly. Statistical analysis revealed a significant relationship between knowledge and condom use (X² = 8.704; df = 1; p = 0.003 < 0.05). It is concluded that there is a statistically significant relationship between both variables.